The Natural History of Untreated Primary Hypogammaglobulinemia in Adults: Implications for the Diagnosis and Treatment of Common Variable Immunodeficiency Disorders (CVID) - Ameratunga, Rohan; Ahn, Yeri; Steele, Richard; Woon, See-Tarn (Frontiers in Immunology, 2019)
Background Adults with hypogammaglobulinemia are frequently encountered by clinicians. Where IgG levels are markedly decreased, most patients are treated with subcutaneous or intravenous immunoglobulin (SCIG/IVIG), because of the presumed risk of severe infections. The natural history of untreated severe asymptomatic hypogammaglobulinemia is thus unknown. Similarly, there are no long-term prospective studies examining the natural history of patients with moderate reductions in IgG. Methods In 2006, we began a prospective cohort study of patients with symptomatic and asymptomatic reductions in IgG who were not immediately commenced on SCIG/IVIG. Over the course of twelve years, one hundred and twenty patients were enrolled in the NZ hypogammaglobulinemia study (NZHS) including fifty-nine who were asymptomatic. Results Five patients with profound hypogammaglobulinemia (IgG < 3 g/l), who were not on regular SCIG/IVIG have remained well for a mean duration of 139 months. This study has also shown most asymptomatic patients with moderate hypogammaglobulinemia (IgG 3.0-6.9 g/l) have been in good health for a mean observation period of 96 months. Only one asymptomatic patient with moderate hypogammaglobulinemia experienced progressive decline in IgG levels to < 3 g/l and was accepted for IVIG replacement. None have suffered catastrophic infections or any of the severe autoimmune or inflammatory sequelae associated with Common Variable Immunodeficiency Disorders (CVID). Unexpectedly, 18.1% of asymptomatic and 41.6% of symptomatic hypogammaglobulinemic patients spontaneously increased their IgG into the normal range (≥ 7.0 g/l) on at least one occasion, which we have termed transient hypogammaglobulinemia of adulthood (THA). In this study, vaccine challenge responses have correlated poorly with symptomatic state and long-term prognosis. Conclusions In spite of our favourable experience, we recommend patients with severe asymptomatic hypogammaglobulinemia are treated with SCIG/IVIG because of the potential risk of severe infections. Patients with moderate asymptomatic hypogammaglobulinemia have a good prognosis. Patients with symptomatic hypogammaglobulinemia are a heterogeneous group where some progress to SCIG/IVIG replacement, while many others spontaneously recover. This study has implications for the diagnosis and treatment of CVID.